Various Approaches in Managing Fish Bone Migration : Our Experience in Tertiary Hospital in Sarawak - Yuanzhi, Cheah; Yew, Ting Ting; Mohd Razif, Mohamad Yunus; Tang, Ing Ping (Springer Nature, 2024)
Fish bone ingestion is one of the common emergencies encountered by the Ear, Nose and Throat (ENT) Department. Most cases can be removed endoscopically. Rarely, surgical intervention may be needed in cases of extraluminal migra- tion of a fish bone [1]. Computed tomography (CT) scans are essential for diagnosing and locating the fish bone and assisting surgical planning [2, 3]. Early surgical interven- tion can prevent serious complications such as oesophageal laceration, and perforation, soft tissue penetration, retropha- ryngeal abscess, neck abscess, mediastinitis, pulmonary and cardiovascular penetration [2, 3]. We report five cases of fish bone migrated extraluminal which required repeat CT scans and various surgical explorations.